Non-Performing Assets in Indian Banks: A Comparative Study: An Analysis of Non-Performing Assets: A Comparative Study of Public, Private, and Foreign Banks in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Non-Performing Assets have been rising swiftly in India, especially in Public Sector Banks which has been affecting the profitability of Banking Sector mostly Public Sector Banks in India. NPAs affect credit lending capacity of Banks which results in low profit for Banks. As the banking sector is the backbone for an economy, rising NPAs is a threat for the Indian economy. This paper tries to understand Non-Performing Assets and reasons behind high NPAs. In this paper, we compare Gross NPA, Growth rate of Gross NPA and Return on Assets of Public Sector Banks, Private Sector Banks and Foreign Banks in India.